Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan Menginap di Hotel Kartika Chandra Jakarta - Jasmani Jasmani; Dede Supiyan; Hastono Hastono (Prodi Manajemen STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of service quality and price on customer satisfaction staying at Hotel Kartika Chandra Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study have a significant effect on customer satisfaction by 46.9%, hypothesis testing is obtained t count > t table or (9,215 > 1,985). Price has a significant effect on customer satisfaction by 44.1%, hypothesis testing is obtained t count > t table or (8,704 > 1,985). Service quality and price simultaneously have a significant effect on customer satisfaction with the regression equation Y = 9.894 + 0.389X1 + 0.369X2 and the contribution of the influence is 54.7%, hypothesis testing is obtained F count > F table or (57,311 > 2,700).